Regular Article-Experimental Physics - de Florian, Daniel; Wagner, Federico; Ali, Ahmed; Kuraev, Eduard A; Bystritskiy, Yury M; Kaidalov, AB; Poghosyan, MG; Yan, Yu-Liang; Dong, Bao-Guo; Zhou, Dai-Mei; others (The European Physical Journal C, 2010)
n/a
n/a